Cruelty against Leniency: The Case of Imperial Zoroastrian Criminal Law - Jany, János (Religions, 2023)
The article examines the impact of Zoroastrianism on criminal law and legal theory during the reign of the Sasanian dynasty (224–651 C.E) in late Antique Persia. This was the historic period when Zoroastrianism was also the ideology of the Iranian state, which granted the Zoroastrian church extraordinary power and influence, a unique situation which is termed by the author as ‘imperial Zoroastrianism’. The first part of the paper examines how imperial Zoroastrianism evolved from previous understanding of religion and law. The second part of the paper scrutinises the Zoroastrian understanding of wrong in the light of eschatology and cosmology, and the ethical principles that follow from this very particular world view. Next, an individual section is devoted to the criminal theory of Zoroastrianism, which regards criminal punishment not as a punishment but as a means to save the soul of the offender from sufferings in Hell. With such an underlying principle in mind, the text looks for examples of cruelty and leniency in substantive criminal law and criminal procedure. This main body of the article examines contemporary legal sources and apocalyptic works. Finally, a comparison of Hindu and Islamic criminal legal theory follows the description of the Zoroastrian criminal law, highlighting astonishing similarities. Considering the results of both the analytic and the comparative methods, the author comes to the conclusion that it is not religion in itself that suppresses crimes, but rather their eschatology and cosmology: religions that are based on divine justice are less lenient toward crimes and offenders than religions in which alternative concepts like divine grace or non-violence are also operative.